АГЛОМЕРАЦИИ КАК СУБЪЕКТ ПОЛИТИКИ В ГЛОБАЛИЗИРУЮЩЕМСЯ МИРЕ - Ревекка Вульфович (Вопросы государственного и муниципального управления, 2016)
Globalization has been changing the urban landscape rapidly in recent decades. Suburbanization, urban sprawl and intensive migration have transformed former territories with a mix of urban and rural settlements into huge high urbanized regions which play a key role in the development of nation states and macro-regions of the world.They have also become sites for the concentration of problems such as terrorism, crime, ethnic conflicts, economic disparities, hatred and exclusion, because of their size and magnetism as points of prosperity.The goal of this article is to show the historical process of agglomeration-building in Europe (e.g. Paris and Berlin), the USA (e.g. Tristate NY) and Russia (e.g. St. Petersburg, Samara – Togliatti Agglomeration) and to explore actual problems of strategic planning in these city-regions. The city-regions are analyzed within the frame of a holistic approach (top – down direction). Large city-agglomerations in Russia are, at present, possible motors of growth and development.The elaboration of strategies for them could be the starting point in the recovery of the economy and society. But the experience in this field is not broad enough to lead to positive and rapid results. This makes a comparative analyses of international examples extremely important for Russian governing bodies and social groups.In the research we use statistical data – demographic, economic and political – to show the strengths, weaknesses, risks and opportunities of agglomeration development in the 21st century.